AGREEMENT ON NEGOTIATING AS NEW INSTITUTE OF THE RUSSIAN CIVIL LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In article the new institute of civil law adopted during reformation of the civil legislation of the Russian Federation - negotiations on signing of the contract is analyzed. Prerequisites in the Russian legislation institute of negotiations, the contractual order of negotiating are considered. The author delimits the agreement on negotiating from other designs preceding the conclusion of the civil contract. In the work the most important terms of agreement abou are analyzed